Frequency of Hyperuricemia in Tuberculosis Patients Treated with Pyrazinamide - Zada, Akhtar; Jamal, Shiraz (Biological and Clinical Sciences Research Journal, 2025)
Tuberculosis (TB) remains a major public health concern, and pyrazinamide is a key component of first-line anti-tuberculosis therapy. However, pyrazinamide is well known to cause hyperuricemia, which may lead to treatment intolerance, arthralgia, and non-compliance. Understanding its frequency and associated risk factors is essential for improving patient management. Objective: To determine the frequency of pyrazinamide-induced hyperuricemia in patients with pulmonary and extrapulmonary tuberculosis in the Medicine Unit of Hayatabad Medical Complex, Peshawar. Methods: This descriptive cross-sectional study included 151 patients aged 18–65 years with confirmed pulmonary or extrapulmonary tuberculosis. All participants had normal baseline renal and liver function tests and serum uric acid levels below 6.5 mg/dL before treatment initiation. Hyperuricemia after four weeks of pyrazinamide-containing anti-TB therapy was defined as serum uric acid >7.0 mg/dL in males and >6.5 mg/dL in females. Data were analyzed using SPSS version 22, with significance set at p < 0.05. Results: The mean age of participants was 42.46 ± 13.11 years, including 85 (56.3%) males. Pulmonary TB was present in 119 (78.8%) patients. Hyperuricemia developed in 72 (47.7%) patients. Significant associations were observed between hyperuricemia and middle age (p = 0.002), male gender (p < 0.001), and prolonged duration of TB before treatment initiation (p = 0.003)—conclusion: Nearly half of the TB patients receiving pyrazinamide developed hyperuricemia. Male gender, middle age, and longer pre-treatment disease duration were significantly associated with risk factors. Routine monitoring of serum uric acid during therapy is recommended to prevent complications and improve treatment adherence.